KAJIAN TEKNIS PENGOPERASIAN CANTRANG DI PERAIRAN BRONDONG, KABUPATEN LAMONGAN, JAWA TIMUR - Mochammad Riyanto; Ari Purbayanto; Wazir Mawardi; Noveldesra Suheri (Institut Pertanian Bogor, 2011)
The use of cantrang grows up as an alternative fishing replacing trawl. Cantrang has different nomenclature used by fishers all Indonesia regions, however there are any regions using the name of cantrang as camouflage of a trawl. National Standardization Agency issued a standard form of cantrang construction (SNI 01-7236-2006) to standardize the gear of cantrang in Indonesia. The objectives of this research are to examine the cantrang construction, and operation aspects of cantrang fisheries in Brondong Waters, Lamongan, East Java. This research was conducted measuring the construction of cantrang, direct by observation following fishing operation trips and interview to the owner and crew of the vessel. The result showed that construction of cantrang in Brondong has differences on some parts to SNI 01-7236-2006, but these differences did not change the form of cantrang. The use of winch to pull the rope is able to accelerate the process of fishing operation thus was increasing the catch.